Borophene integrated MOF-based next-generation sonocatalytic platform: Efficient degradation of organic dyes - Penlik, Yunus; Kekec, Gunseli Guney; Gorduk, Semih (ELSEVIER, 2026)
Water pollution, which has become a critical environmental problem, is increasing daily with industrialization. Textile dyes found in wastewater can be rapidly and efficiently removed without generating waste using sonocatalysis. This promising method allows for degradation using ultrasound-induced cavitation and precursor materials. In this study, the degradation of Rhodamine B (RhB) and Methylene Blue (MB) dyes in aqueous media is achieved using a novel sonocatalyst, Borophene@MIL-101(Fe). This composite system, which incorporates a 2D material and MOF structure, exhibits structural stability, a high active surface area, and an electron transfer capacity under ultrasound vibrations. This system, which enables radical generation and electron transport, was found to operate effectively in a short time. Borophene was first synthesized using the ultrasonic-assisted exfoliation method to achieve this synergistic structure, and MIL-101(Fe) was synthesized using the solvothermal method. A composite of these two material classes was created using a simple mixing method. The XRD, SEM, XPS and FT-IR methods were used for characterization. Parameters such as initial pH, catalyst amount, and initial dye concentration were tested to determine the ideal catalytic environment and amount. Consequently, Borophene@MIL-101(Fe) demonstrated sonocatalytic degradation performance above 85% for both MB and RhB. This new-generation composite sonocatalyst, developed for the removal of polluting dyes from wastewater, is the first of its kind and offers significant insights into the development of composites in this field.
Keywords: Borophene; MIL-101(Fe); Sonocatalysis; Dye degradation; Textile dyes; Ultrasound; HETEROGENEOUS CATALYST; NANOCOMPOSITE; FRAMEWORKS; REMOVAL; OXIDE; Chemistry